Nitrogen-doped K2CO3 modified coffee residue biochar as well as preparation method and application thereof

By performing K2CO3 modification and nitrogen doping treatment on degreased coffee grounds, nitrogen-doped K2CO3 modified coffee ground biochar is prepared with efficient CO2 adsorption, which solves the shortcomings of existing biochar materials in CO2 adsorption efficiency and cost, and realizes an environmentally friendly modification process.

CN119838564APending Publication Date: 2025-04-18JIANGNAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510063582.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing biochar materials have shortcomings in CO2 adsorption efficiency and cost, and toxic chemicals are often used during the preparation process, which affects environmental protection.

Method used

Nitrogen-doped K2CO3 modified coffee ground biochar was prepared by modifying the defatted coffee grounds with K2CO3 and heat treatment under an inert atmosphere, followed by impregnation and heat treatment in an aqueous urea solution.

Benefits of technology

The specific surface area and porosity of biochar are improved, the CO2 adsorption effect is enhanced, the preparation cost is reduced, and the environmental pollution is reduced through environmentally friendly modification methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838564A_ABST
    Figure CN119838564A_ABST
Patent Text Reader

Abstract

The invention discloses a modified defatted coffee residue biochar adsorption material as well as a preparation method and application thereof, and belongs to the technical field of biochar. The biochar adsorption material is formed by compounding and modifying defatted coffee grounds with potassium carbonate and urea, and is applied to CO2 adsorption. The preparation method has the advantages that the potassium carbonate enables the biochar to have larger specific surface area and high porosity, the adsorption sites and the adsorption capacity are increased, and the CO2 adsorption rate is improved. Nitrogen-containing functional groups, such as pyridyl, acylamino, imide, lactam and pyrrolyl, can be introduced into urea through an impregnation method or co-pyrolysis and the like, so that the surface alkalinity of the biochar is improved, and the adsorption efficiency of the biochar is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biochar materials, and in particular relates to nitrogen-doped K2CO3-modified coffee grounds biochar and a preparation method and application thereof. Background Art

[0003] Biochar, as an environmentally friendly and economical CO2 capture material, has attracted extensive attention in the context of "dual carbon". Coffee grounds have high contents of lignin, cellulose and hemicellulose, and are a potential source for making porous biochar. The degreased coffee grounds are prepared into coffee ground biochar for CO2 adsorption, which can realize waste recycling. It is worth noting that compared with other preparation methods such as rapid pyrolysis, hydrothermal carbonization, gasification pyrolysis, etc., slow pyrolysis has the advantages of simple operation and economic feasibility after scale-up. The performance of biochar in adsorbing CO2 is closely related to its raw material source, preparation method and subsequent modification method. However, whether negative carbon benefits can be achieved still needs to be based on detailed research and evaluation, including the use of renewable and low-carbon emission raw materials, such as agricultural waste, coffee grounds, etc., which can improve the negative carbon potential of biochar projects; the process of preparing biochar, the use of low-energy consumption and high-efficiency pyrolysis technology can reduce carbon emissions; the modification process of biochar should choose environmentally friendly methods, reduce the use of toxic chemicals, and optimize operating conditions to reduce energy consumption. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions, including:

[0008] The coffee grounds are pretreated and then degreased, and the degreased coffee grounds and the K2CO3 modifier are ground and mixed evenly, and then heat-treated under an inert atmosphere for a modification, and then washed and dried after the modification to obtain K2CO3-modified coffee grounds biochar;

[0009] The K2CO3-modified coffee grounds biochar is immersed in a urea aqueous solution with a mass percentage concentration of 10 to 30% for 20 to 24 hours, then vacuum-filtered, dehydrated and dried, heat-treated under an inert atmosphere for secondary modification, and washed and dried after the modification is completed to obtain nitrogen-doped K2CO3-modified coffee grounds biochar;

[0010] Wherein, the heat treatment temperature of the secondary modification is 400-600° C., and the heat treatment time is 40-60 min.

[0011] As a preferred embodiment of the method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar of the present invention, the pretreatment includes air drying, grinding, washing, filtration and drying.

[0012] As a preferred scheme for the preparation method of nitrogen-doped K2CO3 modified coffee grounds biochar of the present invention, the degreasing comprises n-hexane and anhydrous ethanol as solvents, the ratio of n-hexane to anhydrous ethanol solvents is 10-15:1, the solid-liquid ratio is 1:1-5g / ml, the degreasing temperature is 70-85°C, and the degreasing time is 1-2h.

[0013] As a preferred embodiment of the method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar of the present invention, the degreasing rate of the defatted coffee grounds is 10-16%.

[0014] As a preferred embodiment of the method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar of the present invention, the mass ratio of the defatted coffee grounds to K2CO3 is 1:1-6.

[0015] As a preferred embodiment of the method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar of the present invention, the heat treatment temperature of the first modification is 700-900°C, and the heat treatment time is 100-120 min.

[0016] As a preferred embodiment of the method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar of the present invention, the inert atmosphere is a nitrogen atmosphere, wherein the gas flow rate is 200-300 ml / min, and the heating rate is 3-5°C / min.

[0017] As a preferred embodiment of the method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar of the present invention, the mass ratio of urea to K2CO3-modified coffee grounds biochar is 1:1-3.

[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide a nitrogen-doped K2CO3-modified coffee grounds biochar.

[0019] As a preferred embodiment of the nitrogen-doped K2CO3-modified coffee grounds biochar of the present invention, the graphitization degree of the nitrogen-doped K2CO3-modified coffee grounds biochar is low, forming an amorphous crystalline structure with a specific surface area of ​​≥2080.1cm 2 / g, total pore volume ≥ 0.9014cm 3 / g, micropore ratio ≥92.85%.

[0020] The third object of the present invention is to overcome the deficiencies in the prior art and provide a method for applying nitrogen-doped K2CO3-modified coffee grounds biochar in the adsorption of CO2.

[0021] Beneficial effects of the present invention:

[0022] (1) The defatted coffee grounds are reused. The cascade utilization not only solves the problem of environmental pollution caused by coffee grounds, but also gives full play to their resource utilization value.

[0023] (2) Provide a novel adsorption material prepared from defatted coffee grounds for adsorbing CO2. The adsorption material has low cost and simple process, overcoming the shortcomings of the current CO2 adsorption material such as high cost and low adsorption rate.

[0024] (3) The K2CO3 selected in the present invention can increase the specific surface area and porosity of biochar; and the basic groups are introduced by nitrogen doping to improve the CO2 adsorption effect of biochar. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0026] Figure 1 Schematic diagram of the preparation process of nitrogen-doped K2CO3-modified coffee grounds biochar.

[0027] Figure 2 X-ray diffraction analysis diagrams of coffee grounds biochar (a), K2CO3-modified coffee grounds biochar (b), and nitrogen-doped K2CO3-modified coffee grounds biochar (c).

[0028] Figure 3 X-ray photoelectron spectra of K2CO3-modified coffee grounds biochar (a) and nitrogen-doped K2CO3-modified coffee grounds biochar (b).

[0029] Figure 4 N1s spectrum of nitrogen-doped K2CO3-modified coffee grounds biochar.

[0030] Figure 5 Scanning electron microscope images of coffee grounds biochar (left), K2CO3-modified coffee grounds biochar (middle), and nitrogen-doped K2CO3-modified coffee grounds biochar (right).

[0031] Figure 6 Figures of nitrogen adsorption-desorption of coffee grounds biochar (a), K2CO3-modified coffee grounds biochar (b), and nitrogen-doped K2CO3-modified coffee grounds biochar (c).

[0032] Figure 7 This is the adsorption capacity diagram of coffee grounds biochar, K2CO3 modified coffee grounds biochar and nitrogen-doped K2CO3 modified coffee grounds biochar materials. DETAILED DESCRIPTION

[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0036] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0037] The coffee grounds were taken from a coffee shop in Yixing City. The variety was 100% Arabica and originated from Brazil. After being packed back to the laboratory, they were placed on trays to dry naturally.

[0038] The performance of the material prepared in the embodiment of the present invention was tested as follows:

[0039] (1) Elemental analysis

[0040] The German Elementar UNICUBE elemental analyzer is used to determine the content of carbon (C), hydrogen (H), sulfur (S) and nitrogen (N) in the material. The measurement accuracy is: the measurement error of carbon, hydrogen and nitrogen does not exceed 0.1%, and the measurement error of sulfur does not exceed 0.2%. The measurement method is: the sample is burned in a high temperature and oxygen-rich environment to decompose it into a mixed gas. These gases are separated by an adsorption-desorption device and then sent to a thermal conductivity cell detector together with a helium carrier gas for analysis and detection.

[0041] (2) X-ray diffractometer (XRD)

[0042] X-ray diffraction can obtain the crystal structure information of the material by measuring the angle distribution and intensity of X-rays after diffraction by the material. Using the D8 ADVANCE model X-ray diffractometer, the powder sample is evenly distributed and compacted, and the detection parameters are set. The scanning range (2θ angle) is 10-80°, the scanning speed is 1° per minute, and the step length is 0.02°. Copper palladium X-rays are used to measure and analyze the diffraction angle and intensity in the diffraction pattern, and the image is analyzed by MDIJade 6 software. Crystal structure information can be inferred.

[0043] (3) X-ray electron spectroscopy (XPS)

[0044] X-ray electron spectroscopy analysis can be used to analyze chemical information within a depth range of about 1 to 10 nm on the surface of a material. Information such as the elemental composition, chemical state, and molecular structure of the sample surface can be obtained from the peak position and peak shape of the XPS spectrum, and the element content or concentration of the sample surface can be obtained from the peak intensity. The present invention uses an X-ray photoelectron spectrometer (Thermo Scientific ESCALAB Xi+, USA) to perform XPS testing on the prepared coffee grounds-based biochar to analyze the nitrogen-containing groups on the surface of the adsorbent.

[0045] (4) Scanning electron microscopy (SEM) analysis

[0046] Scanning electron microscopy is a characterization method for observing the microscopic morphology of samples. The present invention uses a German ZEISSSigma 300 high-resolution scanning electron microscope, which has a magnification of 10 to 1,000,000, an operating voltage of 20V to 30kV, and a resolution of 1.0nm (15kV). Before testing, the sample needs to be treated with gold spraying to make it conductive, and then a small amount of the sample is evenly fixed on a sample table with conductive glue. After N2 purging, the sample morphology is observed under a scanning electron microscope, including the microscopic morphological characteristics of the biochar surface, and semi-quantitative analysis of specific elements is performed.

[0047] (5) Specific surface area and pore structure analysis

[0048] The specific surface area and pore distribution characteristics of biochar were determined using a BELSORP MAX analyzer produced by the Japanese Microtrac MRB manufacturer. The sample needs to be pretreated before measurement. First, it is degassed at 140°C for 3 hours under vacuum conditions, and then the adsorption and desorption test is performed at -196°C with liquid nitrogen as the adsorbent. The specific surface area of ​​the sample is calculated using the Brunauer-Emmett-Teller (BET) model, the mesopore pore size distribution is obtained using the Barrett-Joyner-Halenda (BJH) model, the micropore size distribution is obtained using the Horváth-Kawazoe (HK) model, and the total pore volume is calculated using the N2 adsorption at a relative pressure of 0.99.

[0049] (6) Thermogravimetric analyzer (TGA)

[0050] Thermogravimetric analyzer is an instrument that measures the relationship between the mass of a substance and temperature (or time) under program temperature control. The present invention uses the TGA2 thermogravimetric analyzer produced by Mettler-Toledo to determine the CO2 adsorption capacity of biochar. The experimental steps are to increase the temperature from 25°C to 120°C at 5°C / min under a nitrogen atmosphere (50ml / min), and then perform constant temperature purge for 30 minutes under a nitrogen atmosphere at 120°C. After the end, stop the nitrogen introduction and cool it in a water bath. After cooling to 25°C, introduce CO2 with a purity of 99% for 1 hour, and record the mass change of the whole process. The change in mass within one hour after the temperature drops to 25°C reflects the adsorption capacity of biochar for CO2.

[0051] Example 1

[0052] This embodiment provides a method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar, referring to Figure 1 , specifically:

[0053] After drying the coffee grounds, grind them through a 60-mesh sieve and rinse them with deionized water to remove impurities. Use a water circulation vacuum pump to filter the washed coffee grounds and then place them in a drying oven at 80°C to dry for 24 hours.

[0054] Weigh the dried coffee grounds into a filter paper tube, use anhydrous ethanol and n-hexane as degreasing agents, and degrease under the conditions of solvent ratio of 12:1, solid-liquid ratio of 1:5 g / ml, degreasing temperature of 85°C, and degreasing time of 1 h. After completion, dry the defatted coffee grounds, and the degreasing rate is 15.43%.

[0055] Defatted coffee grounds and potassium carbonate in a mass ratio of 1:1 were weighed and ground. The ground materials were heat treated at 800°C for 120 min in a nitrogen atmosphere with a nitrogen flow rate of 300 ml / min for a modification. After the modification, they were washed with 5wt% hydrochloric acid and then washed with deionized water until neutral. Then, they were dried at 80°C for 24 h and passed through a 200-mesh sieve to obtain K2CO3-modified coffee grounds biochar.

[0056] The K2CO3-modified coffee grounds biochar was stirred and immersed in a 20wt% urea aqueous solution for 24h (the mass ratio of K2CO3-modified coffee grounds biochar and urea was 1:1), and vacuum filtered for dehydration. The dehydrated material was heat treated at 600°C for 60min in a nitrogen atmosphere with a nitrogen flow rate of 300ml / min for secondary modification. After the modification, it was washed with deionized water, dried at 80°C for 24h after removing impurities, and passed through a 200-mesh sieve to obtain the final nitrogen-doped K2CO3-modified coffee grounds biochar.

[0057] The element content of defatted coffee grounds was analyzed, C: 53.25%, H: 8.43%, N: 2.93%. It can be seen that the defatted coffee grounds have a high C content and the H / C ratio is 0.16, which is relatively low, indicating that defatted coffee grounds are a good raw material for preparing biochar.

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 1 is that the defatted coffee grounds are directly heat-treated and carbonized at 800° C. for 2 h without modification and nitrogen doping to obtain coffee grounds biochar.

[0060] Comparative Example 2

[0061] The difference between this comparative example and Example 1 is that no nitrogen doping is performed, only modification is performed, and the rest of the preparation process is the same as that of Example 1 to obtain K2CO3-modified coffee grounds biochar.

[0062] Figure 2 The X-ray diffraction analysis diagram of coffee grounds biochar. Among them, a is defatted coffee grounds biochar, b is K2CO3 modified coffee grounds biochar, and c is nitrogen-doped K2CO3 modified coffee grounds biochar. Compared with coffee grounds biochar, the peak of K2CO3 modified coffee grounds biochar at 2θ=24.38° shifted to the left and the vibration amplitude became lower, indicating that the unit cell parameters of the modified material became larger, the interplanar spacing became larger, and the interlayer spacing increased, destroying the graphitized crystal structure, and having a stronger adsorption capacity for CO2.

[0063] Figure 3 is the X-ray photoelectron spectrum of coffee grounds biochar. Among them, a is K2CO3 modified coffee grounds biochar, b is nitrogen-doped K2CO3 modified coffee grounds biochar, Figure 4It can be seen that a peak line is clearly detected at 398.09 eV in b, which belongs to N1s, indicating that nitrogen doping is successful.

[0064] Figure 4 This is the N1s spectrum of nitrogen-doped K2CO3-modified coffee grounds biochar. The N 1s spectrum mainly includes three peaks, located at 398.4eV, 400.79eV, and 403.56eV, which are pyridinic nitrogen, pyrrolic nitrogen, and nitrogen oxides. Figure 4 It can be seen that only biochar doped with nitrogen has the N1s peak line. This is because during the impregnation process, some carbon atoms are replaced by nitrogen atoms, and due to the introduction of nitrogen, the surface conjugated structure, electron distribution and electrical neutrality of biochar will change, forming pyridine nitrogen, pyrrolic nitrogen and nitrogen oxides.

[0065] Figure 5 The following are scanning electron microscope images of three materials, among which the left one is coffee grounds biochar, the middle one is K2CO3-modified coffee grounds biochar, and the right one is nitrogen-doped K2CO3-modified coffee grounds biochar. As can be seen from the figure, compared with coffee grounds biochar, the K2CO3-modified material shows a relatively disordered folding structure and lacks uniform pores. The amount of visible pores per unit area of ​​the modified biochar is significantly increased, and micropores appear in the macropores, but there are still a few smooth avoidances. After further modification with urea, the pores are more irregular in shape and uneven in size. There are gaps of a certain thickness between the carbon layers, which produce finer particles and pores, providing a large number of adsorption sites for CO2 molecules, thereby improving the adsorption capacity of the material.

[0066] Figure 6 The nitrogen adsorption-desorption diagrams of coffee grounds biochar (a), K2CO3-modified coffee grounds biochar (b), and nitrogen-doped K2CO3-modified coffee grounds biochar (c) are shown in Figure 1. The adsorption-desorption curves of coffee grounds biochar before and after modification conform to the type I isotherm model, and both have a type I hysteresis loop, indicating that there are microporous structures in the composite material. The hysteresis loop in a is not closed, which may be due to the low specific surface area and low porosity of the material itself.

[0067] The specific surface areas of coffee grounds biochar, K2CO3-modified coffee grounds biochar, and nitrogen-doped K2CO3-modified coffee grounds biochar were compared, as shown in Table 1.

[0068] Table 1

[0069]

[0070] By comparing the specific surface area analysis table, it can be seen that the specific surface area and pore volume of nitrogen-doped K2CO3-modified coffee grounds biochar are significantly improved compared with waste coffee grounds, and are higher than ordinary activated carbon adsorption materials. This shows that the composite modifier can increase the specific surface area and pore size of coffee grounds, which is consistent with the conclusion given by SEM. Figure 7 The CO2 adsorption capacity diagram of the above three materials, among which, the maximum adsorption capacity of nitrogen-doped K2CO3 modified coffee grounds biochar is 4.15mmol / g, which is higher than the unmodified and K2CO3 modified biochar, proving that the composite modified coffee grounds adsorption material has better adsorption capacity.

[0071] Comparative Example 3

[0072] The difference between this comparative example and comparative example 2 is that the mass ratio of defatted coffee grounds to K2CO3 is adjusted from 1:1 to 1:3, and the rest of the preparation process is the same as that of comparative example 2 to obtain K2CO3-modified coffee grounds biochar.

[0073] Comparative Example 4

[0074] The difference between this comparative example and comparative example 2 is that the mass ratio of defatted coffee grounds to K2CO3 is adjusted from 1:1 to 1:6 and no nitrogen doping is performed. The rest of the preparation process is the same as that of comparative example 2 to obtain K2CO3-modified coffee grounds biochar.

[0075] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 1 and Comparative Example 2 are shown in Table 2.

[0076] Table 2

[0077]

[0078] It can be seen from the above table that adjusting the mass ratio of defatted coffee grounds to K2CO3 has a significant effect on the performance of K2CO3-modified coffee grounds biochar. This is because the K2CO3 modification process will produce CO, CO2, and potassium vapor, thereby increasing the number of biochar micropores and thus increasing the specific surface area. However, excessive use of K2CO3 will result in high costs and collapse of the pore structure. According to the results in the above table, when the mass ratio of defatted coffee grounds to K2CO3 is 1:1 to 3, the effect is better. Considering the economic cost, the best technical effect can be obtained when the ratio of defatted coffee grounds to K2CO3 in the present invention is 1:1.

[0079] Comparative Example 5

[0080] The difference between this comparative example and comparative example 2 is that no degreasing is performed, that is, the degreasing rate of the coffee grounds is 0%, and the rest of the preparation process is the same as that of comparative example 2 to obtain K2CO3-modified coffee grounds biochar.

[0081] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 1 and Comparative Example 2 are shown in Table 3.

[0082] Table 3

[0083]

[0084] As can be seen from the above table, adjusting the degreasing rate has a significant effect on the performance of K2CO3 modified coffee grounds biochar, because the polyunsaturated fat in the coffee grounds polymerizes to form heavier non-volatile resins, which will block the pores formed during the K2CO3 modification process. According to the results in the above table, the best technical effect can be obtained when the degreasing rate in the present invention is 15.43%.

[0085] Comparative Example 6

[0086] The difference between this embodiment and embodiment 1 is that the nitrogen doping method is adjusted to be in-situ nitrogen doping, and the rest of the preparation process is the same as that of embodiment 1 to obtain nitrogen-doped K2CO3-modified coffee grounds biochar.

[0087] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 1 are shown in Table 4.

[0088] Table 4

[0089]

[0090]

[0091] As can be seen from the above table, adjusting the nitrogen doping method has a significant effect on the performance of nitrogen-doped K2CO3-modified coffee grounds biochar. This is because in-situ nitrogen doping is directly impregnated with urea solution by defatted coffee grounds, and the pore structure of defatted coffee grounds is inferior to that of K2CO3-modified coffee grounds, so the doping effect is inferior to post-treatment nitrogen doping. The best technical effect can be obtained when the nitrogen doping method in the present invention is post-treatment nitrogen doping.

[0092] Comparative Example 7

[0093] The coffee grounds were dried at 110 °C overnight and sieved to obtain particles with a regular size of 180-425 μm, recorded as CG. CG and K2CO3 powders were thoroughly mixed in a mortar at a mass ratio of 1:1. The mixture was then placed in a tube furnace and heated to 600 °C at a rate of 5 °C / min under a N2 flow rate of 200 mL / min for pyrolysis for 1 h. After pyrolysis, the sample was cooled to room temperature, washed with 1 M HCl, and then washed several times with distilled water on the filter until the pH of the filtrate was close to neutral. Finally, the sample was dried in an oven at 110 °C overnight.

[0094] Comparative Example 8

[0095] The coffee grounds were dried at 110 °C overnight and sieved to obtain particles with a regular size of 180-425 μm, recorded as CG. CG and K2CO3 powders were thoroughly mixed in a mortar at a mass ratio of 1:5. The mixture was then placed in a tube furnace and heated to 600 °C at a rate of 5 °C / min under a N2 flow rate of 200 mL / min for pyrolysis for 1 h. After pyrolysis, the sample was cooled to room temperature, washed with 1 M HCl, and then washed several times with distilled water on the filter until the pH of the filtrate was close to neutral. Finally, the sample was dried in an oven at 110 °C overnight.

[0096] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 1 are shown in Table 5.

[0097] Table 5

[0098]

[0099]

[0100] Note: “-” means no data.

[0101] As can be seen from the above table, the potassium carbonate used in the present invention can make the biochar have a larger specific surface area and high porosity, increase the adsorption sites and adsorption capacity, and improve the CO2 adsorption rate. Urea can introduce nitrogen-containing functional groups such as pyridine, amide, imide, lactam and pyrrol through impregnation or co-pyrolysis, thereby increasing the surface alkalinity of biochar and thus improving the adsorption efficiency of biochar.

[0102] In summary, the present invention reuses the defatted coffee grounds, and the step-by-step utilization not only solves the problem of environmental pollution caused by coffee grounds, but also gives full play to its resource utilization value. The K2CO3 selected in the present invention can increase the specific surface area and porosity of biochar; and the basic groups are introduced by nitrogen doping to improve the CO2 adsorption effect of biochar.

[0103] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar, characterized in that: include, The coffee grounds are pretreated and then degreased, the degreased coffee grounds and the K2CO3 modifier are ground and mixed evenly, and then heat-treated under an inert atmosphere for a modification, and then washed and dried after the modification to obtain K2CO3-modified coffee grounds biochar; The K2CO3-modified coffee grounds biochar is immersed in a urea aqueous solution with a mass percentage concentration of 10 to 30% for 20 to 24 hours, then vacuum-filtered, dehydrated and dried, heat-treated under an inert atmosphere for secondary modification, and washed and dried after the modification is completed to obtain nitrogen-doped K2CO3-modified coffee grounds biochar; Wherein, the heat treatment temperature of the secondary modification is 400-600° C., and the heat treatment time is 40-60 min.

2. The method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar according to claim 1, characterized in that: The pretreatment includes air drying, grinding, washing, suction filtration and drying.

3. The method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar according to claim 1, characterized in that: The degreasing process uses n-hexane and anhydrous ethanol as solvents, the ratio of n-hexane to anhydrous ethanol is 10-15:1, the solid-liquid ratio is 1:1-5 g / ml, the degreasing temperature is 70-85° C., and the degreasing time is 1-2 hours.

4. The method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar according to claim 3, characterized in that: The defatted coffee grounds have a defatting rate of 10-16%.

5. The method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar according to claim 1, characterized in that: The mass ratio of the defatted coffee grounds to K2CO3 is 1:1-6.

6. The method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar according to claim 1, characterized in that: The heat treatment temperature of the primary modification is 700-900° C., and the heat treatment time is 100-120 minutes.

7. The method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar according to claim 1, characterized in that: The inert atmosphere is a nitrogen atmosphere, wherein the gas flow rate is 200-300 ml / min, and the heating rate is 3-5° C. / min.

8. The method for preparing nitrogen-doped K2CO3-modified coffee grounds biochar according to claim 1, characterized in that: The mass ratio of the urea to the K2CO3-modified coffee grounds biochar is 1:1-3.

9. A nitrogen-doped K2CO3-modified coffee grounds biochar prepared by the method of claim 1, characterized in that: The nitrogen-doped K2CO3-modified coffee grounds biochar has a low graphitization degree, forms an amorphous crystalline structure, and has a specific surface area of ​​≥2080.1cm 2 / g, total pore volume ≥ 0.9014cm 3 / g, micropore ratio ≥92.85%.

10. Use of the nitrogen-doped K2CO3-modified coffee grounds biochar as claimed in claim 9 in adsorbing CO2.

Citation Information

Patent Citations

  • Preparation method of coffee ground activated carbon

    CN105217629A

  • Nitrogen-doped biochar as well as preparation method and application thereof

    CN115043479A

  • Preparation method and application of hydrothermal nitrogen-doped cork-based activated carbon

    CN115974076A

  • Formed Charcoal Comprising Coffee Wastes And Method Thereof

    KR1020150104684A